Insulating foamed lightweight cementitious composite with co-addition of micro-sized aerogel and hydrogen peroxide. (19th December 2022) - Tan, Tee How; Shah, Syed Nasir; Ng, Chin Chong; Putra, Azma; Othman, Muhammad Nur; Mo, Kim Hung
Highlights: Co-addition of aerogel and hydrogen peroxide in FLCC. FLCC has oven-dry density as low as 380 kg/m 3 and a strength of about 3 MPa. Thermal conductivity of FLCC decreased significantly up to 0.15 W/m·K. FLCC has improved sound insulation with an α value of 0.24–0.55. Abstract: Noise pollution and thermal discomfort are major concerns in urban areas these days. The building sector consumes a large amount of total energy to fulfill the thermal comfort demands, which are rapidly increasing with modern advancements. The overwhelming energy demand and noise pollution prevalent in the building sector can be controlled using insulating cementitious composites. Therefore, this research investigates the properties of foamed lightweight cementitious composite (FLCC) which incorporates the co-addition of micro-sized aerogel and hydrogen peroxide. Different contents of aerogel (0.5%, 1%, and 1.5% by weight of cement) were used as additives along with various dosages of hydrogen peroxide (1%, 2%, and 3% by weight of cement) to produce the FLCC. The optimum content of the FLCC comprising 1% aerogel and 3% hydrogen peroxide, has a low oven-dry density of 380 kg/m 3 with an adequate compressive strength (about 3 MPa) for application as an insulating cementitious composite. The high porosity characteristic (up to 76%) of the FLCC improved sound absorption and thermal conductivity (reduction by 88%). Overall, the results highlighted the promising role of aerogel and hydrogen peroxide incorporated FLCC as a useful insulating construction material.